Staff Guidance Note on Macroprudential Policy : Detailed Guidance on Instruments. (Policy Papers; Policy Paper ;, 2014)
This note covers considerations that can guide the staff's policy advice on the use of a broad range of macroprudential tools. It discusses the transmission and likely effectiveness of these tools in mitigating systemic risks and the set of indicators that can be used in surveillance to assess the need for changes in macroprudential policy settings. This note is a supplement to the Staff Guidance Note on Macroprudential Policy.